A chimpanzee enamel-diet δ13C enrichment factor and a refined enamel sampling strategy: Implications for dietary reconstructions. Issue 159 (October 2021) - Malone, Maire A.; MacLatchy, Laura M.; Mitani, John C.; Kityo, Robert; Kingston, John D.
Abstract: Reconstructing diets from stable carbon isotopic signals in enamel bioapatite requires the application of a δ 13 C enamel-diet enrichment factor, or the isotopic offset between diet and enamel, which has not been empirically determined for any primate. In this study, an enamel-diet enrichment factor (ε∗enamel-diet ) of 11.8 ± 0.3‰ is calculated for chimpanzees ( Pan troglodytes ) at Ngogo in Kibale National Park, Uganda, based on a comprehensive isotopic assessment of previously analyzed dietary plant data and new isotopic analyses of enamel apatite. Different enamel sampling methods are evaluated to determine the potential influence of weaning on isotopic enamel values and dietary interpretations. The new chimpanzee enrichment factor and a sampling strategy that excludes teeth that formed before weaning completion are applied to all known chimpanzee δ 13 Cenamel data, either previously published or newly derived in this study, resulting in a dietary range of almost 6‰ across all chimpanzees sampled. This new chimpanzee enamel-diet enrichment factor is then used to reassess dietary reconstructions of 12 fossil hominin species whose isotopic enamel signatures have been determined. Results reveal hominin diets that are isotopically more positive than previously reconstructed, highlighting the widespread contribution of 13 C-enriched C4 /crassulacean acid metabolism (CAM) resources in fossil hominin diets and emphasizing the broad use of these resources during human evolution. These findings stress the importance of ascertaining and employing an appropriate enrichment factor for dietary reconstructions of specific taxa as well as standardizing the sampling protocol for tooth enamel in isotopic paleodietary reconstructions.